'McDonald's Music' Versus 'Serious Music': How Production and Consumption Practices Help to Reproduce Class Inequality in the Classical Music Profession. (September 2017) - Bull, Anna; Scharff, Christina
This article draws on two empirical studies on contemporary engagements with classical music in the United Kingdom to shed light on the ways in which class inequalities are reproduced in practices of production and consumption. It discusses three ways in which this occurs. First, classical music was 'naturally' practiced and listened to in middle-class homes but this was misrecognised by musicians who labelled families as 'musical' rather than as 'middle class'. Second, the practices of classical music production and consumption such as the spaces used, the dress, and the modes of listening show similarities with middle-class culture. Third, musicians made judgements of value where classical music was seen as more valuable than other genres. This was particularly visible in studying production. In data on consumption, musicians were careful about making judgements of taste but described urban genres as illegible to them, or assessed them according to the criteria that they used to judge classical music, such as complexity and emotional depth. This hierarchy of value tended to remain unspoken and uncontested. Studying production and consumption together allows these patterns to emerge more clearly.